2012
DOI: 10.1890/11-1583.1
|View full text |Cite
|
Sign up to set email alerts
|

Insect herbivory and propagule pressure influence Cirsium vulgare invasiveness across the landscape

Abstract: Abstract. A current challenge in ecology is to better understand the magnitude, variation, and interaction in the factors that limit the invasiveness of exotic species. We conducted a factorial experiment involving herbivore manipulation (insecticide-in-water vs. water-only control) and seven densities of introduced nonnative Cirsium vulgare (bull thistle) seed. The experiment was repeated with two seed cohorts at eight grassland sites uninvaded by C. vulgare in the central Great Plains, USA. Herbivory by nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 22 publications
(48 reference statements)
3
25
0
Order By: Relevance
“…Those model results suggested a growing C. vulgare population that was inconsistent with quantitative field observations (Andersen and Louda 2008). Our first experiment showed that greater propagule pressure and experimental reduction of herbivory led to the highest initial C. vulgare seedling density (Eckberg et al 2012); however, in that study we did not evaluate the effects of herbivory on plant population growth. In this study, we experimentally introduced C. vulgare into multiple currently uninvaded grassland sites in Lancaster and Saunders Counties, Nebraska, USA.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…Those model results suggested a growing C. vulgare population that was inconsistent with quantitative field observations (Andersen and Louda 2008). Our first experiment showed that greater propagule pressure and experimental reduction of herbivory led to the highest initial C. vulgare seedling density (Eckberg et al 2012); however, in that study we did not evaluate the effects of herbivory on plant population growth. In this study, we experimentally introduced C. vulgare into multiple currently uninvaded grassland sites in Lancaster and Saunders Counties, Nebraska, USA.…”
Section: Introductionmentioning
confidence: 88%
“…This approach precludes a rigorous assessment of the effects of native insect herbivory (biotic resistance) on the critical initial phase of invasion: plant population establishment. Our previous study showed that herbivory significantly reduced the rate at which the Eurasian C. vulgare seedlings invaded new grasslands, an effect that intensified with lower propagule pressure (Eckberg et al 2012). However, the effect of herbivory on population growth rate for newly established C. vulgare invasions remains unknown.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations